2011
DOI: 10.5194/asr-6-245-2011
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbines in icing conditions: performance and prediction

Abstract: Abstract. Icing on structures is an important issue for wind energy developments in many regions of the world. Unfortunately, information about icing conditions is mostly rare due to a lack of measurements. Additionally, there is not much known about the operation of wind turbines in icing conditions. It is the aim of the current study to investigate the effect of icing on power production and to evaluate the potential of icing forecasts to help optimizing wind turbine operation.A test site with two Enercon E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 10 publications
(11 reference statements)
1
11
0
1
Order By: Relevance
“…This shows that in more moderate terrain like in the Jura region grid sizes around 2 km are sufficient to capture the most important terrain features. This result is confirmed by other studies in the Jura region (Dierer et al, 2011). The values given in the icing map for regions with very complex terrain (e.g., the Alps) must therefore not be interpreted as a local result but should rather be seen as rough indication for regional icing risk.…”
Section: Discussionsupporting
confidence: 86%
“…This shows that in more moderate terrain like in the Jura region grid sizes around 2 km are sufficient to capture the most important terrain features. This result is confirmed by other studies in the Jura region (Dierer et al, 2011). The values given in the icing map for regions with very complex terrain (e.g., the Alps) must therefore not be interpreted as a local result but should rather be seen as rough indication for regional icing risk.…”
Section: Discussionsupporting
confidence: 86%
“…The challenge of atmospheric icing has also been studied for wind energy, with several international collaborations on the topic (e.g., Fikke et al 2006;Ronsten et al 2012), as well as a dedicated conference on wind energy in cold climates (Winterwind International Wind Energy Conference). The use of mesoscale models to estimate icing has been applied for studies in aviation (e.g., Thompson et al 1997;Wolff et al 2009), for both power-line icing and turbine icing in the power industry (e.g., Fikke et al 2008;Dierer et al 2011), and for comparisons with icing on standard cylinders (Bernstein et al 2012;Byrkjedal 2012a,b;Soderberg and Baltscheffsky 2012;Yang 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few conference presentations on forecasting icing at Winterwind, but these have mostly focused on forecasting ice on a standard cylinder using the Makkonen (2000) model and then relating the standard icing results to the turbine using statistical algorithms (e.g., Dierer et al 2011;Byrkjedal 2012a;Soderberg and Baltscheffsky 2012;Yang 2012). Bernstein et al (2012) reported that the correlation between measured icing load on a cylinder and actual power loss is weak because significant ice loads may persist on cylinders while power recovers at the turbines.…”
Section: Introductionmentioning
confidence: 99%
“…and Europe where there are annual averages of more than fifty days of icing conditions. Atmospheric icing causes problems for wind turbine operation in cold climates [1] through: (1) reducing the energy production by lowering the aerodynamic efficiency [2] of the rotor, (2) reducing the life expectancy of the turbine by increasing the fatigue and mass imbalance on the structure, (3) ice shedding from the blades which can be dangerous to nearby *This work was supported in part by a Center for Research and Education in Wind (CREW) seed grant. The authors thank Dr. Patrick Moriarty of the U.S. National Renewable Energy Laboratory for providing a blade part for our test setup.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also thank Fiona Dunne for feedback on earlier drafts of this paper. 1 S. Shajiee is a Ph.D. student in the Department of Aerospace Engineering Sciences, University of Colorado, Boulder, CO 80309. property, personnel, or livestock, (4) wind turbine down times, (5) electrical failure in different components, and (6) creating measurement errors in wind speed and direction. Current indirect ice sensing methods, which measure temperature, humidity, and power output do not have enough spatial resolution for active de-icing; and predictions of icing conditions based on these measurements are generally not very accurate.…”
Section: Introductionmentioning
confidence: 99%